2011
DOI: 10.1074/jbc.m110.186353
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Lipid Droplet Composition by Direct Organelle Mass Spectrometry

Abstract: An expanding appreciation for the varied functions of neutral lipids in cellular organisms relies on a more detailed understanding of the mechanisms of lipid production and packaging into cytosolic lipid droplets (LDs). Conventional lipid profiling procedures involve the analysis of tissue extracts and consequently lack cellular or subcellular resolution. Here, we report an approach that combines the visualization of individual LDs, microphase extraction of lipid components from droplets, and the direct identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…2 C and F-H). Because validation of Nile red staining in the meristem tissues by mass spectrometry is difficult because of technique limitations, we applied another commonly used lipid dye, Bodipy 493/503 (47), in the same condition. Our results showed that the signal intensity of lipid droplets stained by Bodipy dye was reduced significantly in rpl4d and tirT mutants, similar to the result from Nile red staining (Fig.…”
Section: Rpl4 Mutation Resulted In Reduced Lipid Accumulation In Merimentioning
confidence: 99%
“…2 C and F-H). Because validation of Nile red staining in the meristem tissues by mass spectrometry is difficult because of technique limitations, we applied another commonly used lipid dye, Bodipy 493/503 (47), in the same condition. Our results showed that the signal intensity of lipid droplets stained by Bodipy dye was reduced significantly in rpl4d and tirT mutants, similar to the result from Nile red staining (Fig.…”
Section: Rpl4 Mutation Resulted In Reduced Lipid Accumulation In Merimentioning
confidence: 99%
“…To address these questions, technological advances are needed to isolate speckles either biochemically or microscopically, which can then be analyzed using the available highly sensitive proteomic methods. Recently, single lipid droplets from cytoplasm were isolated by combining visualization and microphase separation to analyze their composition (Horn et al, 2011). A similar approach might be useful in analyzing the composition of speckles.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Perhaps future comparisons of transcriptional profi les between oil palm fruit and seeds (two adjacent tissue systems rich in lipid droplets, one without and one with oleosins), with an eye toward lipid-droplet biogenesis, may provide insights into the generalized and/or unique machinery involved in TAG packaging in plants. These studies will likely be complemented by proteomics analysis of LDs as well as emerging techniques for analyzing the lipid composition (i.e., lipidome) of individual LDs ( 112,113 ).…”
Section: Approaches To Identify Novel Proteins Involved In Ld Biogenementioning
confidence: 99%